SOLID LIPID NANOPARTICLES: A PROMISING APPROACH FOR COMBINATIONAL DRUG THERAPY IN CANCER - Lala, Rita R.; Shinde, Amol S.; Nandvikar, Nikita Y. (International Journal of Applied Pharmaceutics, 2018)
Combination therapy for cancer treatment is accepted worldwide due to the generation of synergistic anticancer effects; restrain in multidrug resistance (MDR) or tumor resistance by different mechanisms of action and minimization of dose-dependent toxicity. Recently developed Solid lipid nanoparticles (SLNs) are matrix composed of lipid which is solid at both room and body temperature and hence it is as an alternative to other nanocarrier systems. SLNs after oral administration get absorbed by lymphatic pathway due to stimulation of chylomicron formation. Thus, it avoids all consequences related to an oral drug delivery system and improves oral bioavailability. SLNs based combination drug delivery to tumor tissues reduces the problems associated with chemotherapy. The targeted and sustained delivery of chemotherapeutic agents reduces the dose by achieving high concentrations at the target site, without altering the normal tissues. In this article, we have reviewed and focused on SLNs as a drug delivery system; ingredients used in formulating SLNs and developed two or more drugs in a single formulation of SLNs as drug delivery. This article also focuses on the fact that SLNs as a combination drug delivery provides an attractive approach in future prevention and beneficial for the treatment of cancer by increasing its therapeutic efficacy.